Intravaginal treatment features of vulvovaginal candidiasis in women - K Kurbanovna Mirzabalaeva; Yu V Dolgo-Saburova (IP Berlin A.V., 2013)
This article describes the features of the various forms of intravaginal treatment of vulvovaginal candidiasis (VVC). Effectiveness of topical treatment of acute VVC is about 90% and is not significantly different from the effectiveness of systemic antifungal agents. Use of a single dose of fungicidal imidazoles, such as 2 % butoconazole nitrate cream ensures maximum adherence and high efficiency of treatment as well as relief of acute exacerbation of recurrent VVC. Weekly use of 5 g of 2% butoconazole nitrate cream for preventing recurrent VVC can be an alternative to the use of systemic antifungal drugs.